Design and optimisation of skin stiffened aircraft structures - Selvamurugan Ramya Priyadarsini (2018)
With the demand for highly efficient structural panels for aircraft applications, there is a need to manufacture better stiffened panels at lower cost and lower weights without compromising their capability to withstand in-plane and out-of-plane loading. Stiffened panels can withstand higher loads and have better damage tolerance than the conventional non-strengthened panels. Composite materials have been widely used for manufacturing of these panels which can yield additional weight saving without sacrificing specific strength and stiffness. Hence optimising these stiffened structures are crucial and is vastly studied. Optimising the stiffened panels can be done through their design variables or the geometrical variables such as the dimensions of the stiffener, material variables such as the material used for manufacturing the stiffeners, the type of composite fibres used for the skin, etc. There are also variable structural properties like the composite laminate stacking sequence, the thickness of each ply, etc. For optimisation, these variables are subjected to simulations, which use various combinations of the variables to find the optimum output parameter which can yield better performance of a structural panel under low weight conditions. Apart from the structural optimisation, there is a need for manufacturing optimisation as well, which can help manufacture better structures at low cost. Better performance with lower weight and cost reduction are the main objectives for optimisation of the stiffened panels. This dissertation aims to provide structural optimisation for a stiffened composite sandwich panel by using a reliable and fully automated optimisation software that can utilise a wide range of optimisation and statistical analysis methods. The structural stiffened panel under consideration in a helicopter tail unit was modelled and subjected to Finite Element Analysis in Abaqus to estimate the Von -Mises stress distribution and the buckling loads with their corresponding Eigen values. The necessary output values were noted, and then automated optimisation was carried out using Isight software. The stacking angle of the composite panel skin was considered to be the only design variable and then the orientation angles were varied to obtain the best combination of the stacking ply angles using Non – dominated Sorting Genetic Algorithm (NSGA – II) that produced the optimal results. The obtained results were validated by using the obtained input parameters into Abaqus and noting the tolerance. The results show the best ply stacking sequence to obtain the optimal results with no change in the weight of the structure.